A new way of measuring behavioural compliance for prevention programme interventions using KAP Score. Issue 4 (19th May 2019) - Lindgren, Daniel; Kelley, Shawn
ABSTRACT: KAP Score is an evaluation tool developed to enable aid and donor organisations to monitor and evaluate the outcome of interventions, particularly those where the link between programme activities and outcomes constitutes an "unknown". This article articulates KAP Score and demonstrates how it has been applied to two separate interventions related to risk avoidance (human trafficking) and demand reduction (wildlife consumption) to generate quantitative evidence for assessing how they contributed to increasing compliance. The examples presented demonstrate how KAP Score attributed the effectiveness of these interventions to a proxy indicator that can measure incremental behavioural compliance.